Marriage in a panic: Panic disorder and intimate relationships - Kasalova, Petra; Prasko, Jan; Holubova, Michaela; Vanek, Jakub; Ociskova, Marie; Minarikova, Kamila; Chupacova, Michaela; Kantor, Krystof; Kolek, Antonín; Sollár, Tomáš; Nesnidal, Vlastimil; Zatkova, Marta; et al. (Neuro endocrinology letters, 2020)
BACKGROUND: Panic disorder and agoraphobia not only affect the patients themselves but also may have a detrimental effect on their intimate relationships. A problem arising in the intimate sphere could be a trigger, a modulator, a maintenance factor, or the result of the panic disorder and agoraphobia. The consequences of panic disorder include increased demands on the non-affected partner to adapt, which may prove to be too challenging for some to manage. Panic disorder and agoraphobia can also change earlier relationship patterns which may result in partnership dysfunction. This review explores the effect of panic disorder and agoraphobia upon partnership problems and satisfaction. METHOD: Relevant studies were identified via PubMed and Web of Science, published between January 1970 and April 2020. The search terms included "panic disorder", "agoraphobia", "marital problems", "marital conflicts" and "marital adjustment". Further references were found in reviews, books, and book chapters of the relevant papers. A total of 1154 articles were nominated by primary assortment using the keywords in different combinations. After selecting according to the inclusion and exclusion criteria, evaluating the complete texts and searching for secondary documents, 173 papers were finally chosen. RESULTS: Problems in a relationship can act as a trigger for the development of the panic disorder and agoraphobia and could also function as modulating and maintenance factors. Panic disorder and agoraphobia often have a negative influence on the relationship and the non-affected partner. Partnership problems can be both a precursor and a consequence of panic disorder and agoraphobia.
Keywords: Panic Disorder; Marriage; lidé; Personal Satisfaction; panická porucha; Agoraphobia; osobní uspokojení; Family Conflict; agorafobie; konflikt v rodině; manželství; Humans